Experiences of Patients With COVID-19 Admitted to the Intensive Care Units: A Qualitative Study - Norouzadeh, Reza (J Patient Exp, 2021)
This study aimed to describe the experiences of patients with COVID-19 admitted to the intensive care units (ICU). The data were analyzed by content analysis on 16 ICU patients with COVID-19. Data were collected by semi-structured interviews. Three categories were identified: (a) captured by a challenging incident with subcategories: perceived sudden and challenging death, fear of carelessness in overcrowding, worry about the family, and frustration with stigmatizing; (b) the flourishing of life with subcategories: spiritual-awakening, resilience in the face of life challenges, promoting health behaviors, and striving for recovery; and (c) honoring the blessings with subcategories: understanding the importance of nurses, realizing the value of family, and realizing the value of altruism. COVID-19 survivors experienced both positive and negative experiences. The results of this study could help health care providers identify the needs of ICU patients with COVID-19, including psychological, social, and spiritual support and design care models.